1 ms^-2=____kmh^-2. explain it
Answers
Answered by
9
1 km = 1000 m
1 / 1000 km = m
1 / 10³ km = m
10^{ - 3 } km = m ------: ( 1 )
h = 60 minutes
h = 60 × 60 seconds
h = 3600 s
h² = ( 3600 )² s²
h² / ( 3600 )² = s²
( 3600 )² / h² = 1 / s²
( 3600 )² / h² = s^{ - 2 }
( 3600 )² × h^{ - 2 } = s^{ - 2 }-------: ( 2 )
Therefore ,
1 ms^{ - 1 }
From ( 1 ) and ( 2 ) ,
= > 1 × 10^{ - 3 } km × { 3600 }² × h^{ - 2 }
![= > {10}^{ - 3} \times (36 \times 100) {}^{2} \: \: \: km {h}^{ - 2} \\ \\ = > 1 {0}^{ - 3} \times {36}^{2} \times {100}^{2} \: \: km {h}^{ - 2} \\ \\ = > {10 }^{ - 3} \times {36}^{2} \times {10}^{4} \: \: km {h}^{ - 2} \\ \\ = > {36}^{2} \times 10 \: \: km {h}^{ - 2} \\ \\ = > 1296 \times 10 \: \: km {h}^{ - 2} \\ \\ = > 12960 \: km {h}^{ - 2} = > {10}^{ - 3} \times (36 \times 100) {}^{2} \: \: \: km {h}^{ - 2} \\ \\ = > 1 {0}^{ - 3} \times {36}^{2} \times {100}^{2} \: \: km {h}^{ - 2} \\ \\ = > {10 }^{ - 3} \times {36}^{2} \times {10}^{4} \: \: km {h}^{ - 2} \\ \\ = > {36}^{2} \times 10 \: \: km {h}^{ - 2} \\ \\ = > 1296 \times 10 \: \: km {h}^{ - 2} \\ \\ = > 12960 \: km {h}^{ - 2}](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%7B10%7D%5E%7B+-+3%7D+%5Ctimes+%2836+%5Ctimes+100%29+%7B%7D%5E%7B2%7D+%5C%3A+%5C%3A+%5C%3A+km+%7Bh%7D%5E%7B+-+2%7D+%5C%5C+%5C%5C+%3D+%26gt%3B+1+%7B0%7D%5E%7B+-+3%7D+%5Ctimes+%7B36%7D%5E%7B2%7D+%5Ctimes+%7B100%7D%5E%7B2%7D+%5C%3A+%5C%3A+km+%7Bh%7D%5E%7B+-+2%7D+%5C%5C+%5C%5C+%3D+%26gt%3B+%7B10+%7D%5E%7B+-+3%7D+%5Ctimes+%7B36%7D%5E%7B2%7D+%5Ctimes+%7B10%7D%5E%7B4%7D+%5C%3A+%5C%3A+km+%7Bh%7D%5E%7B+-+2%7D+%5C%5C+%5C%5C+%3D+%26gt%3B+%7B36%7D%5E%7B2%7D+%5Ctimes+10+%5C%3A+%5C%3A+km+%7Bh%7D%5E%7B+-+2%7D+%5C%5C+%5C%5C+%3D+%26gt%3B+1296+%5Ctimes+10+%5C%3A+%5C%3A+km+%7Bh%7D%5E%7B+-+2%7D+%5C%5C+%5C%5C+%3D+%26gt%3B+12960+%5C%3A+km+%7Bh%7D%5E%7B+-+2%7D+)
Hence,
1 ms^{ - 2 } = 12960 km h^{ - 2 }
1 / 1000 km = m
1 / 10³ km = m
10^{ - 3 } km = m ------: ( 1 )
h = 60 minutes
h = 60 × 60 seconds
h = 3600 s
h² = ( 3600 )² s²
h² / ( 3600 )² = s²
( 3600 )² / h² = 1 / s²
( 3600 )² / h² = s^{ - 2 }
( 3600 )² × h^{ - 2 } = s^{ - 2 }-------: ( 2 )
Therefore ,
1 ms^{ - 1 }
From ( 1 ) and ( 2 ) ,
= > 1 × 10^{ - 3 } km × { 3600 }² × h^{ - 2 }
Hence,
1 ms^{ - 2 } = 12960 km h^{ - 2 }
Similar questions